Population pharmacokinetics of exendin‐(9‐39) and clinical dose selection in patients with congenital hyperinsulinism. (6th December 2017) - Ng, Chee M.; Tang, Fei; Seeholzer, Steven H.; Zou, Yixuan; De León, Diva D.
Abstract : Aims: Congenital hyperinsulinism (HI) is the most common cause of persistent hypoglycaemia in infants and children. Exendin‐(9‐39), an inverse glucagon‐like peptide 1 (GLP‐1) agonist, is a novel therapeutic agent for HI that has demonstrated glucose‐raising effect. We report the first population pharmacokinetic (PopPK) model of the exendin‐(9‐39) in patients with HI and propose the optimal dosing regimen for future clinical trials in neonates with HI. Methods: A total of 182 pharmacokinetic (PK) observations from 26 subjects in three clinical studies were included for constructing the PopPK model using first order conditional estimation (FOCE) with interaction method in nonlinear mixed‐effects modelling (NONMEM). Exposure metrics (area under the curve [AUC] and maximum plasma concentration [ C max ]) at no observed adverse effect levels (NOAELs) in rats and dogs were determined in toxicology studies. Results: Observed concentration–time profiles of exendin‐(9‐39) were described by a linear two‐compartmental PK model. Following allometric scaling of PK parameters, age and creatinine clearance did not significantly affect clearance. The calculated clearance and elimination half‐life for adult subjects with median weight of 69 kg were 11.8 l h −1 and 1.81 h, respectively. The maximum recommended starting dose determined from modelling and simulation based on the AUC0‐last at the NOAEL and predicted AUC0‐inf using the PopPK model was 27 mg kg −1 day −1 intravenously. Conclusions: This is the first study to investigate the PopPK of exendin‐(9‐39) in humans. The final PopPK model was successfully used with preclinical toxicology findings to propose the optimal dosing regimen of exendin‐(9‐39) for clinical studies in neonates with HI, allowing for a more targeted dosing approach to achieve desired glycaemic response.